EVALUATION OF ANXIOLYTIC POTENTIAL OF VARIOUS EXTRACTS OF TAMARINDUS INDICA FLOWERS - VUYYALA, BALAKRISHNA; KUMAR D, SENTHIL; LAKSHMI, THAKKALAPALLY (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of this study was designed to gauge the antianxiety activity of varied extracts, namely, n-hexane, chloroform, ethyl acetate, and methanol of the flowers of Tamarindus indica using elevated plus maze (EPM) model in albino mice. Methods: Coarsely powdered tamarind was powdered and subjected to exhaustive Soxhlet extraction using n-hexane, chloroform, ethyl acetate, and methanol. Solvents were recovered from all extracts using a rotary vacuum evaporator under reduced pressure. Albino mice have ministered orally with different doses of the extracts (i.e., 200 and 400 mg/kg) and behavior was observed on the EPM. The standard (positive control) employed in the study Diazepam (2 mg/kg, P.O). Results: Results indicate that the methanol extract of T. indica flowers showed maximum and significant dose-dependent effect at 200 and 400 mg/kg on EPM, the results were just like the standard antianxiety agent diazepam (2 mg/kg). Locomotor activity evaluated with two different doses of T. indica (200 and 400 mg/kg) using actophotometer. The results were shown to be decreased in a dose dependent model compared to control. Conclusion: The methanol extract shows that the presence of polyphenols could be liable for the anxiolytic potential of T. indica. Hence, this plant could also be used as a useful antianxiety agent.